Molecular Simulation for Screening Bioactive Compounds as Potential Candidate for Alzheimer’s Disease - Immanuelle Kezia; Linda Erlina; Ninik Mudjihartini; Fadilah Fadilah (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
Alzheimer’s disease is one of the neurodegenerative diseases that afflict the elderly. One of the symptoms is a loss cognitive ability due to neuronal death caused by amyloid plaque accumulation. Alzheimer’s disease is one of the most expensive diseases to treat. Drugs for Alzheimer’s treatment only treat the symptoms, not the disease itself. Several pathways, including the mitochondrial cascade, can be used to develop drugs for Alzheimer’s disease, according to NIH guidelines. Caspase3 is a protein that involved in the mitochondrial cascade, specifically in apoptosis. Alzheimer’s therapy may be more effective if caspase3 is targeted. Indonesia is a rich country, particularly in medicinal plants. We used the Structure-Based Drug Design approaches to screen bioactive compounds in Indonesian medicinal plant to find the best compound candidate. In addition, we performed ADMETOX prediction, molecular docking, and molecular dynamic simulation on forty 3D structures of bioactive compounds and donepezil as an FDA approved Alzheimer’s drug. We discovered Miraxanthin-V had a higher binding affinity than donepezil using molecular simulation. As a result, we can conclude that Miraxanthin-V has a high potential of neuroprotective by inhibiting apoptosis.